Brief exposure of neonatal testis cells to EGF or GDNF alters the regenerated tissue - Awang Junaidi, Awang Hazmi; Fayaz, Mohammad Amin; Goldstein, Savannah; Honaramooz, Ali (Bioscientifica, 2022)
We have previously shown that implantation of testis cell aggregates under the back skin of immunodeficient mice results in de novo regeneration of testis tissue. We used this unique model to investigate the effects of epidermal growth factor (EGF) and glial cell-derived neurotrophic factor (GDNF) on testis cord development. Neonatal piglet testis cells were briefly (<1 h) exposed to either low (L: 0.02 μg/mL) or high (H: 2 μg/mL) doses of EGF, GDNF, or vehicle (control), before implantation in recipient mice. Randomly selected implants were removed from each mouse at 1, 2, 4, and 8 weeks post-implantation. GDNF-L implants showed increased testis cord development over time, and EGF-L implants had increased cross-sectional area. The ratio of regular cords decreased over time in EGF-H and GDNF-H implants and was replaced by a higher ratio of irregular cords in GDNF-H. EGF-L and GDNF-H implants were quickest to display rete testis-like structures. Overall, the lower dose of each growth factor was more effective than its higher dose in improving the implantation outcomes. This is the first comprehensive assessment of these key growth factors on de novo formation (regeneration) of testis tissue.